Workforce Diversity at Work: Exploring Ethnicity as Moderating in Age and Performance - Mahat, Dipak (PT FORMOSA CENDEKIA GLOBAL, 2024)
It’s critical to promote workplace employee diversity, as it empowers various workforces and improves teamwork. Adopting employee diversity fosters a positive work atmosphere that encourages employee creativity and productivity. Based on this background, the aim of the study was to understand teaching faculty perceptions of age, ethnicity, and performance and to analyse the moderating effect of ethnicity on age and performance. The study was objective in nature, focusing on private colleges in the Kathmandu Valley of Nepal to select teaching faculty. A cross-sectional design was adopted, ensuring a snapshot of data collection. Consent and privacy were maintained throughout the study, respecting participants' confidentiality. The study identifies ethnicity as a moderating factor between age and performance, where age and ethnicity separately enhance performance but ethnicity as a moderating factor interacts negatively. While age has a positive relationship with performance, ethnicity as a moderator displays a subtle yet significant negative impact on job performance. Colleges must address both the advantages of age diversity and the ethnic imbalances in order to encourage equal opportunities and boost overall productivity.